The Effect of Level of Wheat Inclusion in Diets for Growing and Finishing Pigs on Performance, Nutrient Digestibility and Gastric Ulceration - M. E. E. Ball; E. Magowan (Asian-Australasian Journal of Animal Sciences, 2012)
Four experimental diets were formulated to contain 700 g/kg cereal with decreasing levels of wheat:barley inclusion. Diet 1 contained 700 g/kg wheat, diet 2 contained 600 g/kg wheat and 100 g/kg barley, diet 3 contained 500 g/kg wheat and 200 g/kg barley and diet 4 contained 400 g/kg wheat and 300 g/kg barley. The diets were offered to pigs on three trials to investigate effects on the performance of individually (n = 72) and group housed (n = 480) pigs and on nutrient digestibility in pigs housed in metabolizm crates (n = 24). Performance was assessed from 10 wks of age until slaughter and carcass characteristics were measured. For the group performance study, one pig from each pen (in total 24) at 10, 15 wks and at finish were slaughtered to ascertain scores for stomach ulceration, stomach weights and intestinal length. Level of wheat inclusion did not significantly (p>0.05) affect liveweight gain (LWG) or feed conversion ratio (FCR). Feed intake was lowest (p<0.05) for individually housed pigs offered diets containing 700 g/kg wheat during the 10–15 wk period, which indicated that individually housed pigs attempted to eat to a constant energy intake. There was little evidence of stomach ulceration across treatments and increasing wheat inclusion had no detrimental effect. Higher levels of wheat inclusion tended to increase backfat depth at the P2 position which could lead to increasing grading penalties in a commercial situation although more research is required in this area. Increasing level of wheat inclusion increased digestible energy (DE) content but the lack of effect on FCR and killing out percentage indicated that utilization of energy from barley and wheat was similar. Digestibility coefficients increased linearly with increasing wheat content, which can be attributed to the lower level of fibre and higher level of starch in wheat compared with barley.